2021
DOI: 10.1111/1541-4337.12713
|View full text |Cite
|
Sign up to set email alerts
|

Prolamin‐based complexes: Structure design and food‐related applications

Abstract: Prolamins are a group of safe food additives that are biocompatible, biodegradable, and sustainable. Zein, gliadin, kafirin, and hordein are common prolamins that have been extensively studied, particularly as these form colloidal particles because of their amphiphilic properties. Prolamin‐based binary/ternary complexes, which have stable physicochemical properties and superior functionality, are formed by combining prolamins with polysaccharides, polyphenols, water‐soluble proteins, and surfactants. Although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 201 publications
(378 reference statements)
0
20
0
Order By: Relevance
“…These drawbacks of zein may limit the application of it in the food industry. Researches have demonstrated that the physicochemical and functional properties of prolamin can be modulated by interacting with polyphenols (Song et al., 2021). For instance, zein–resveratrol conjugates exhibited much higher antioxidant activity, thermal stability, and emulsify activity than those of unmodified zein (Ren et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…These drawbacks of zein may limit the application of it in the food industry. Researches have demonstrated that the physicochemical and functional properties of prolamin can be modulated by interacting with polyphenols (Song et al., 2021). For instance, zein–resveratrol conjugates exhibited much higher antioxidant activity, thermal stability, and emulsify activity than those of unmodified zein (Ren et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Storage proteins from cereals, such as prolamins which are chemically characterized as containing a large amount of proline and glutamine amino acids (J. Song et al., 2021; Tapia‐Hernández et al., 2019) also can be used as delivery systems for different bioactive compound especially because their amphiphilic properties facilitate the formation of micro/nanoparticles (J. Song et al., 2021).…”
Section: Anthocyanin Bioaccessibility and Bioavailability In Anthocya...mentioning
confidence: 99%
“…38 Besides, prolamin presents particular advantages such as the flexible fabrication potential; superior stability against various physical, chemical, and environmental stresses (e.g., pH, salt, temperature, heating); strong affinity toward bioactive compounds; and biocompatibility, biodegradability, and sustainability features. 32 Therefore, prolamins are promising candidates for architecturing biocompatible and eco-friendly porous films. However, currently available techniques for the preparation of prolamin-based film that have been widely reported such as the electrospinning and SEIPS method are poor in production efficiency and fine control over the microstructural characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…From the large library of the naturally occurring biopolymers, prolamins, a fascinating group of plant-based storage proteins (zein, kafirin, hordein, gliadin, secalin, and avenin derived from corn, sorghum, barley, wheat, oat, and rye, respectively), are characterized by the high proportion of nonpolar amino acids (40–80%) and peculiar solubility (soluble in 60–90% alcohol, 100% acetic acid, and alkaline solutions). , Because of the amphiphilic properties, prolamin could self-assemble into numerous high-order structures including nanospheres, nanofibers, nanoribbons, and films under fine control. For example, prolamin-based nano- or microparticles were widely fabricated using the antisolvent precipitation technique, wherein prolamins dissolved in stock solutions (60–90% alcohol–water solution or 70–85% acetic acid–water solution) were dropped into an antisolvent (water). By increasing the prolamin concentration in the stock solution or tuning the antisolvent conditions, the assemblies of prolamin could be evolved from particles to fibers .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation